2017
DOI: 10.1177/1753193417728406
|View full text |Cite
|
Sign up to set email alerts
|

The effect of adding active flexion to modified Kleinert regime on outcomes for zone 1 to 3 flexor tendon repairs. A prospective randomized trial

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 51 publications
0
17
1
4
Order By: Relevance
“…Moriya et al (2016b) also observed no bowstringing clinically after releasing the entire A2 pulley and flexor tendon repair in zone 2c. Other surgeons have recorded no clinically notable bowstringing after partial or completed division of A2 or A4 pulleys as well (Elliot et al, 2016;Rigó et al, 2017;Tang, 2005Tang, , 2013Tang, , 2014Tang et al, 2013Tang et al, , 2014Tang et al, , 2017Wu and Tang, 2014;Zhou et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Moriya et al (2016b) also observed no bowstringing clinically after releasing the entire A2 pulley and flexor tendon repair in zone 2c. Other surgeons have recorded no clinically notable bowstringing after partial or completed division of A2 or A4 pulleys as well (Elliot et al, 2016;Rigó et al, 2017;Tang, 2005Tang, , 2013Tang, , 2014Tang et al, 2013Tang et al, , 2014Tang et al, , 2017Wu and Tang, 2014;Zhou et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As such, for the less experienced surgeon, the extra-tendinous modification may be the better repair method to use. Currently, there are many other suture configurations using looped sutures (Moriya et al, 2015(Moriya et al, , 2016a(Moriya et al, , 2016bPan et al, 2017;Rigó et al, 2017;Savage and Tang, 2016;Tang, 2007;Wu and Tang, 2014;Zhou et al, 2017). Further studies might include comparing these techniques in repeated cyclic loading conditions or different suture materials.…”
Section: Discussionmentioning
confidence: 99%
“…Stronger suture materials without increased diameter are desirable. Fiberwire, however, seems to be too stiff (Giesen et al, 2017(Giesen et al, , 2018Hay et al, 2017;Rigó et al, 2017), and many surgeons do not consider it suitable for zone 2 flexor tendon repair.…”
Section: Future Perspectivesmentioning
confidence: 99%